Multikink solutions and deformed defects - Brito, Gustavo Pazzini de [UNESP]; Dutra, Alvaro de Souza [UNESP] (Elsevier B.V., 2014)
In this work we consider an application of the deformation procedure that enables us to construct, systematically, scalar field models supporting multikinlcs. We introduce a new deformation function in order to realize this task. We exemplify the procedure with three different starting models already known in the literature, and the resulting deformed models have rich minima structures which are responsible for the appearance of multikink configurations. We have also considered an application to braneworld scenarios, where we have obtained interesting configurations corresponding to the multikink solutions. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Kink; Multikink; Deformed defect; Topological defect